Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s13199-015-0313-7
|View full text |Cite
|
Sign up to set email alerts
|

The growth of tomato seedlings inoculated with co-cultivated Piriformospora indica and Bacillus pumilus

Abstract: A novel co-culture method using the beneficial root endophytic fungus Piriformospora indica and a plant-growth promoting rhizobacterial strain of Bacillus pumilus to promote the growth of tomato seedlings in plug trays, is described. Coconut water, a waste product from the coconut industry, was used as medium for co-cultivation of the two biological agents. During the co-culture with the fungus, the bacterial strain showed a similar growth rate to that in monoculture in fresh autoclaved coconut water. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
(56 reference statements)
1
18
0
Order By: Relevance
“…Anith et al . () also reported that inoculation with B. pumilus improved the plant growth compared to the uninoculated control (Anith et al . ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Anith et al . () also reported that inoculation with B. pumilus improved the plant growth compared to the uninoculated control (Anith et al . ).…”
Section: Discussionmentioning
confidence: 92%
“…() also reported that inoculation with B. pumilus improved the plant growth compared to the uninoculated control (Anith et al . ). Inoculation of rice seedlings with B. pumilus increased the leaf K + , Ca 2+ and Mg 2+ concentrations, while decreasing the Na + uptake as compared to the uninoculated control (Khan et al .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The plants inoculated only with pathogen spore suspension FOC were termed as positive control. After 24-h plants were transferred to the greenhouse for 1–2 weeks for disease development as described by Kim et al (2001) and Anith et al (2015). This individual experiment was conducted in Randomized Complete Design with five replications and the whole experiment was repeated two times.…”
Section: Methodsmentioning
confidence: 99%
“…For this coconut water collected from a local coconut processing unit was filtered using muslin cloth to avoid dirt and debries.100ml of it was transferred to a 500 ml Erlenmeyer flask, the pH was adjusted to 6.5 and the solution was sterilized by Autoclaving at 121 °C for 20 minute. For preparing CWA, 2% agar was added before autoclaving (Anith et al, 2015). (Anith et al, 2015).…”
Section: Cultivation Of Fungal and Bacterial Strainmentioning
confidence: 99%